Rancang Bangun Aplikasi Sistem Pakar Berbasis Android untuk Identifikasi Penyakit pada Gigi dengan Menggunakan Metode Forward Chaining - Johan Limantono; Rinabi Tanamal (Teknik Informatika Universitas Pamulang, 2020)
Teeth are an important part of the body in the digestive process. As a start of the digestive process, teeth receive various kinds of food conditions such as sweet, cold, hard foods, and so on. These food conditions affect dental health so that when teeth are not treated they become vulnerable to disease. Society in general does not pay attention to pain in the teeth. Though the pain in the teeth can be caused by diseases such as dental caries, tartar, and others. The solution of this research is manifested in the form of an expert system to diagnose dental diseases using the Android-based Forward Chaining method. The expert system application used by researchers is McGoo. The purpose of this expert system is to help the public get information and carry out a diagnosis of dental disease independently. Users only need to answer the questions displayed by the system to get the results of the diagnosis in the form of the type of illness and treatment solutions that can be done. The results of the system diagnosis have been tested and validated by experts namely dentists who are the source of information and data. Based on the accuracy of the system diagnostic test results are by the results of the expert diagnosis.